The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1248/cpb.c12-00270
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Loaded Zein <i>in Situ</i> Gel for Interstitial Chemotherapy

Abstract: A novel drug delivery system of doxorubicin (DOX)-loaded Zein in situ gel for interstitial chemotherapy was investigated in this study. The possible mechanisms of drug release were described according to morphological analysis by optical microscopy and scanning electronic microscope (SEM). In vitro and in vivo anti-tumor activity studies showed that DOX-loaded Zein in situ gel was superior to DOX solution. Local pharmacokinetics in tumor tissue was studied by quantitative analysis with confocal laser scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Zein exhibits high potential to form hydrogels with or without linking to the other polymers to form 3D brick-like structures with sufficient space to host biomolecules [288]. Most of the zein-based hydrogels have been used for drug delivery applications in which the gelation and entrapment of biomolecules are carried out in a single stage resulting in a so-called 'in situ gels' [312,313]. For chemotherapy and site-specific delivery, zein-based smart in situ hydrogels have been developed with the capability of protecting the therapeutic agents from the harsh and unfavourable environment with the potential to respond to the external stimuli like heating, ionic strength, and pH [314].…”
Section: Preparation and Characterization Of Zein Hydrogelsmentioning
confidence: 99%
“…Zein exhibits high potential to form hydrogels with or without linking to the other polymers to form 3D brick-like structures with sufficient space to host biomolecules [288]. Most of the zein-based hydrogels have been used for drug delivery applications in which the gelation and entrapment of biomolecules are carried out in a single stage resulting in a so-called 'in situ gels' [312,313]. For chemotherapy and site-specific delivery, zein-based smart in situ hydrogels have been developed with the capability of protecting the therapeutic agents from the harsh and unfavourable environment with the potential to respond to the external stimuli like heating, ionic strength, and pH [314].…”
Section: Preparation and Characterization Of Zein Hydrogelsmentioning
confidence: 99%
“…Zein hydrogels have also been designed for sustained release of chemotherapeutics and reduce their off-target effects. Cao et al demonstrated that an intratumoral injection of an in situ zein hydrogel extended the release of entrapped DOX, resulting in increased anti-tumor efficacy [ 465 ]. They also showed that DOX release could be modulated by adjusting the zein concentration [ 465 ].…”
Section: Applications In Drug Deliverymentioning
confidence: 99%
“…Doxorubicin hydrochloride (DOX) is one of the most commonly used anticancer drugs in chemotherapy and is widely used by many researchers in different drug delivery systems . However, many side effects of DOX, including cardiotoxicity, drug resistance, loss of appetite and alopecia, have limited its clinical application .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Doxorubicin hydrochloride (DOX) is one of the most commonly used anticancer drugs in chemotherapy and is widely used by many researchers in different drug delivery systems. [12][13][14][15] However, many side effects of DOX, including cardiotoxicity, drug resistance, loss of appetite and alopecia, have limited its clinical application. [13] Therefore, effective DOX drug delivery systems should be developed to improve tumour targeting and reduce systemic side effects.…”
Section: Introductionmentioning
confidence: 99%